The Utility of an Online Forward Triage Tool During the SARS-CoV-2 Pandemic: Health Care Provider and Health Authority Perspectives - Michel, Janet; Kilb, Tim S.; Mettler, Annette; Müller, Martin; Hautz, Wolf E.; Hautz, Stefanie C.; Sauter, Thomas C. (Frontiers in Public Health, 2022)
Introduction: The SARS COV-2 pandemic poses major challenges not only to patients but also to health care professionals and policy-makers, with rapidly changing, sometimes complex, recommendations and guidelines to the population. Online forward triage tools (OFTT) got a major boost from the pandemic as they helped with the implementation and monitoring of recommendations. Methods: A multiphase mixed method sequential explanatory study design was employed. Quantitative data were collected first and informed the qualitative interview guides. Video interviews were held with key informants (health care providers and health authorities) between 2 September and 10 December 2020. Audio-recordings were transcribed verbatim, coded thematically and compared with patient perspectives (framework). Objectives: To explore the perspectives of health care providers and authorities in Canton Bern on the utility of a COVID-19 OFTT, as well as elicit recommendations for telehealth in future. Results: The following themes emerged; i) accessibility ii) health system burden reduction iii) utility in preventing onward transmission iv) utility in allaying fear and anxiety v) medical decision-making utility vi) utility as information source vii) utility in planning and systems thinking. The health care providers and health authorities further provided insights on potential barriers and facilitators of telehealth in future. Conclusion: Similar to patients, health care providers acknowledge the potential and utility of the COVID-19 OFTT particularly as an information source and in reducing the health system burden. Data privacy, doctor-patient relationship, resistance to change, regulatory and mandate issues and lack of systems thinking were revealed as barriers to COVID-19 OFTT utility.